PERAN PEREMPUAN DALAM PENERAPAN URBAN FARMING UNTUK MENINGKATKAN KETAHANAN PANGAN DAN KETANGGUHAN KELUARGA DI KELURAHAN PASIE NAN TIGO DAN PADANG SARAI - Rinawati (LPPM Universitas Ekasakti, 2024)
This study examines the significant role of women in the implementation of urban farming to enhance food security and family resilience in the Pasie Nan Tigo and Padang Sarai villages. Urban farming emerges as a vital solution in urban areas facing challenges such as climate change and rapid urbanization. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess women's participation in urban farming activities. The findings indicate that 75% of the surveyed women actively engage in urban farming, leading to increased food availability and improved economic independence within households. However, challenges such as limited knowledge of farming techniques and access to quality resources were identified. This study highlights the necessity of strengthening women's roles in urban farming initiatives as a community-based climate adaptation strategy, ultimately contributing to enhanced food security and resilience against natural disasters.